A U-shaped dose–response of carbohydrate–protein supplementation on rowing performance - Wang, Xiangyu; Wu, Hao (Frontiers in Nutrition, 2025)
Background and aimCo-ingestion of carbohydrate and protein supplement (CHO–PRO) is a common strategy to enhance endurance performance. However, the optimal dose–response relationship has not been established, which limits evidence-based nutritional guidance for individuals. This study aimed to characterize the performance dose–response curve of a 4:1 CHO–PRO during prolonged rowing.MethodsIn a randomized, double-blind, parallel-group trial, 171 physically active male university students (age: 23 ± 2 years) from non-sports majors each completed a single experimental session. Each session involved a rowing protocol consisting of two 30-min bouts. During the exercise, participants consumed one of eight distinct doses of a 4:1 CHO–PRO in aliquots every 15 min. The CHO delivery rates ranged from 0.5 to 1.2 g/kg/h. Total rowing distance served as the primary performance outcome and was analyzed using a one-way ANCOVA with baseline countermovement jump as a covariate.ResultA significant quadratic (U-shaped) dose–response relationship was found for rowing performance. The lowest dose CHO–PRO (0.5 g/kg/h CHO) resulted in significantly greater rowing distance compared to several higher doses (0.9–1.2 g/kg/h). No significant main effect of supplement dose was observed for heart rate, blood lactate, blood glucose, or rating of perceived exertion during exercise. Post-exercise recovery markers also did not differ significantly between the groups.ConclusionFor prolonged rowing, a lower dose of the CHO–PRO was more effective than higher doses, revealing a non-linear performance response. This non-linear response was characterized by significant performance decrements at several higher intake levels. These findings underscore the importance of dose optimization. Exceeding a certain intake threshold may impair endurance performance.